PRACTISING CURRICULUM MANAGEMENT: THE IMPLEMENTATION OF INTEGRATED CURRICULUM MANAGEMENT IN ISLAMIC SCHOOL - Edi Yulianto; Agus Zaenul Fitri (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2021)
Chongraksat Wittaya School Pattani, Thailand, is one of the most prominent Islamic schools in Pattani, Southern Thailand. This school has a dualism of management, including the applied curriculum, namely the religious and academic curriculum. Although the Thai kingdom regulates these two curricula, schools can adapt to their needs for religious curricula. This article examines the planning, implementation, and evaluation of the curriculum at Chongraksat Wittaya School Pattani, Thailand. It uses a qualitative method and a phenomenological approach with data collecting from interviews, observation, and documentation techniques. Then, data analysis techniques consist of data reduction, model data, and conclusions. The results showed that the Chongraksat Wittaya school implemented an integrated curriculum, namely the religious curriculum (Sassanah), which contained Dirasah Islamiyah, and the academic curriculum (Saman) included general subject matter. This school has regular classes and special classes. Curriculum planning is carried out together with Village Experts at the beginning of each semester. The curriculum is implemented with 40% of the religious curriculum (Sassanah) and 60% of the academic curriculum (Saman). Evaluation is carried out by briefings, daily meetings, early semester meetings, and annual meetings. Student learning is in the form of numeric and descriptive. The evaluation of the model uses the CIPP (Context, Input, Process, and Product) model.